Effect of post-ruminal guanidinoacetic acid supplementation on creatine synthesis and plasma homocysteine concentrations in cattle. (10th March 2020) - Ardalan, Mehrnaz; Batista, Erick D; Titgemeyer, Evan C
Abstract: Creatine stores high-energy phosphate bonds in muscle, which is critical for muscle activity. In animals, creatine is synthesized in the liver from guanidinoacetic acid (GAA ) with methylation by S -adenosylmethionine. Because methyl groups are used for the conversion of GAA to creatine, methyl group deficiency may occur as a result of GAA supplementation. With this study, the metabolic responses of cattle to post-ruminal supplementation of GAA were evaluated with and without methionine (Met ) supplementation as a source of methyl groups. Six ruminally cannulated Holstein heifers (520 kg) were used in a split-plot design with treatments arranged as a 2 × 5 factorial. The main plot treatments were 0 or 12 g/d of l -Met arranged in a completely randomized design; three heifers received each main plot treatment throughout the entire experiment. Subplot treatments were 0, 10, 20, 30, and 40 g/d of GAA, with GAA treatments provided in sequence from lowest to highest over five 6-d periods. Treatments were infused continuously to the abomasum. Heifers were limit-fed twice daily a diet consisting of (dry matter basis) 5.3 kg/d rolled corn, 3.6 kg/d alfalfa hay, and 50 g/d trace-mineralized salt. Plasma Met increased ( P < 0.01) when Met was supplemented, but it was not affected by supplemental GAA. Supplementing GAA linearly increased plasma arginine (% of total amino acids) and plasma concentrations of GAA and creatinine ( P < 0.001). Plasma creatine was increased at all levels of GAA except when 40 g/d of GAA was supplemented with no Met (GAA-quadratic × Met, P = 0.07). Plasma homocysteine was not affected by GAA supplementation when heifers received 12 g/d Met, but it was increased when 30 or 40 g/d of GAA was supplemented without Met (GAA-linear × Met, P = 0.003); increases were modest and did not suggest a dangerous hyperhomocysteinemia. Urinary concentrations of GAA and creatine were increased by all levels of GAA when 12 g/d Met was supplemented; increasing GAA supplementation up to 30 g/d without Met increased urinary GAA and creatine concentrations, but 40 g/d GAA did not affect urine concentrations of GAA and creatine when no Met was supplemented. Overall, post-ruminal GAA supplementation increased creatine supply to cattle. A methyl group deficiency, demonstrated by modest increases in plasma homocysteine, became apparent when 30 or 40 g/d of GAA was supplemented, but it was ameliorated by 12 g/d Met.